Late Prehistoric Hunter-Gatherers and Farmers of the Jornada Mogollon - Kenmotsu, Nancy Adele; Rocek, Thomas R. (Book collections on Project MUSE., 2018)
"The Jornada branch of the Mogollon culture in southeastern part of the U.S. and northern edge of Mexico played significant economic, political, and social roles. Topics reach beyond the American Southwest, such as mobility, forager adaptations, transition to farming, responses to environment, and patterns of social interaction"--Provided by publisher